HTPC: HORÁRIO DE TRABALHO PEDAGÓGICO COLETIVO OU HORÁRIO DE TRABALHO PERDIDO? - Sousa, Paula Raquel Gonçalves de (2007)
This research investigated the events that occurred in the collective time of pedagogical work- HTPC- at public schools in the estate educational system in relation to continuing formation of teachers. Therefore, it was made a historical salvage of HTPC and looked for verifying which actions were being developed in this time in order to analyze if this space is, in fact, used as continuing formation purpose or its institutionalization became an obligation that contributes to resistance of the characters involved. The qualitative investigation was realized at an estate school in Santo Andre, municipality of Sao Paulo, through a case study. The meetings were observed during a semester of 2006 and became scenes that were the analysis base for understanding what activities were realized. The study also used as investigation instruments, semi structured interview with the coordinator teacher and questionnaire for the teachers group, aiming to verify their conceptions about the continuing formation and the events occurred in order to determine agreements and disagreements between theory and practice.(AU)